HONEYBEE PRODUCTION SYSTEM, CHALLENGES AND OPPORTUNITIES IN SELECTED DISTRICTS OF GEDEO ZONE, SOUTHERN NATION, NATIONALITIES AND PEOPLES REGIONAL STATE, ETHIOPIA - Gebretsadik, Teklu; Negash, Dinku (International Journal of Research -GRANTHAALAYAH, 2016)
The study was carried out in selected districts of Gedeo zones of southern Nation nationality and people’s regional state: such as Wonago, Kochere and DillaZuria/chichu/ districts. The objective of the study was to asses production systems, opportunities and constraints of apiculture farming in Gedeo zones of SNNPRs. Beekeeping is a long-standing practice in the study districts and appears as ancient history of the country as a whole. A cross sectional study, in which 90 households were purposively included and conducted in selected district to assess the current beekeeping practices, production potentials and production constraints. Most (72%) of the beekeepers in the study area have owned only traditional hives and produce honey for home consumption. The beekeeping practice was dominated by male. Despite the area have production constraints, the area opportunities like existence of large sized natural forest and artificial forest, due attention provision from regional, federal and local government and nongovernmental organizations, yearly flowering and variety floral availability, some small scale farmers highly experienced in apiculture farming, market access and high demand of apicultural products at nationally and international level. Therefore, Designing effective honeybee pests and predators controlling methods, Introduction of full package improved beekeeping technologies with adequate practical skill training on all bee keeping trends and queen rearing practices promoting beekeepers important indigenous knowledge, Producing areal major honeybee plants in large scale, Avoiding discarding of bee colonies after honey harvest, Availing the strategies to support farmers with beekeeping business support services, Improving pre- and post-harvest handling of bee products and Improving the utilization of stingless bee’s resources, without damaging the colony is important to make the honey production system in the area more economical, so as to enhance bee products for national and international need.